1977
DOI: 10.1037/0022-006x.45.5.949
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the schizophrenia-organicity scale with brain-damaged and non-brain-damaged schizophrenics.

Abstract: Watson had developed a Schizophrenia-Organicity (Sc-0) Minnesota Multiphasic Personality Inventory scale that successfully distinguished schizophrenic from braindamaged patients. The present study used this Sc-0 scale to distinguish organically impaired schizophrenics from nonimpaired schizophrenics. Forty-eight schizophrenic subjects were divided into the organic and nonorganic groups by findings from both their Halstead-Reitan Impairment rating and the physical neurological examination. £-test analyses and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…We therefore suggested that the scale's discriminating power probably lay primarily in its ability to detect functional pathology rather than in a relationship with traits unique to brain damage. Several later authors (e.g., Andersen, Felling, & Seitz, 1970;Halperin, Neuringer, Davies, & Goldstein, 1977;Holland, Lowenfeld, & Wadsworth, 1975;Ruff, Ayers, & Templer, 1977) confirmed this speculation.…”
Section: Sc-0 Scalementioning
confidence: 86%
See 1 more Smart Citation
“…We therefore suggested that the scale's discriminating power probably lay primarily in its ability to detect functional pathology rather than in a relationship with traits unique to brain damage. Several later authors (e.g., Andersen, Felling, & Seitz, 1970;Halperin, Neuringer, Davies, & Goldstein, 1977;Holland, Lowenfeld, & Wadsworth, 1975;Ruff, Ayers, & Templer, 1977) confirmed this speculation.…”
Section: Sc-0 Scalementioning
confidence: 86%
“…While the Golden, Sweet, and Osmon paper documents the ability of the scale to separate brain-damaged from schizophrenic patients, the hit rates reported were lower than those in any previous study on male Ss. Halperin et al (1977) attempted to determine whether SC-0 could differentiate brain-damaged schizophrenics from schizophrenics without brain disorders. They compared the Sc-0 scores of schizophrenics with high and low Halstead impairment index "his error is not limited to the Ruff-Ayers-Templer group.…”
mentioning
confidence: 99%